2021
DOI: 10.1113/jp281875
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neural drive to calf muscles during steady submaximal contractions after repeated static stretches

Abstract: support-information-section). Key pointsr Repeated static-stretching interventions consistently increase the range of motion about a joint and decrease total joint stiffness, but findings on the changes in muscle and connective-tissue properties are mixed.r The influence of these stretch-induced changes on muscle function at submaximal forces is unknown. To address this gap in knowledge, the changes in neural drive to the plantar flexor muscles after a static-stretch intervention were estimated.r Neural drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Hence, small changes in firing rate can reveal statistical significance. Recent interventional studies have demonstrated this, where firing rate can change significantly by ∼0.5 Hz through muscle stretching (Mazzo et al., 2021) and by 0.33–0.64 Hz with vibration‐induced reciprocal inhibition (Mesquita et al., 2022; Orssatto et al., 2022) when using HDsEMG techniques. However, it is important to note that each reported finding is not exclusive to human models, but also consistent with experiments using animal preparations and cellular studies.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, small changes in firing rate can reveal statistical significance. Recent interventional studies have demonstrated this, where firing rate can change significantly by ∼0.5 Hz through muscle stretching (Mazzo et al., 2021) and by 0.33–0.64 Hz with vibration‐induced reciprocal inhibition (Mesquita et al., 2022; Orssatto et al., 2022) when using HDsEMG techniques. However, it is important to note that each reported finding is not exclusive to human models, but also consistent with experiments using animal preparations and cellular studies.…”
Section: Discussionmentioning
confidence: 96%
“…The change in the percentage of motor units associated with the shared modes after both interventions (Table 3) likely reflect a shift in distribution of inputs delivered by premotor interneurons. The shift may be mediated by a change in afferent feedback after the two interventions (Baudry & Duchateau, 2014; Guissard & Duchateau, 2006; Loram et al., 2009; Mazzo et al., 2021). This change is supported by the depression of spinal reflex excitability due to reductions in the feedback signals transmitted by group Ia afferents after static stretching (Guissard & Duchateau, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our study reports a computational analysis of a motor unit dataset acquired by Mazzo and colleagues in a previous study (Mazzo et al., 2021). Briefly, participants performed isometric contractions with the plantar flexor muscles on each of two visits to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations